2015
DOI: 10.1093/nar/gkv185
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of miR-21 by phage display screened peptide

Abstract: miRNAs are nodal regulators of gene expression and deregulation of miRNAs is causally associated with different diseases, including cancer. Modulation of miRNA expression is thus of therapeutic importance. Small molecules are currently being explored for their potential to downregulate miRNAs. Peptides have shown to have better potency and selectivity toward their targets but their potential in targeting and modulating miRNAs remain unexplored. Herein, using phage display we found a very selective peptide agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 57 publications
2
44
0
4
Order By: Relevance
“…In 15 N- 1 H HSQC spectra recorded at 5C, we also observed four weak and broad peaks with chemical shift values corresponding to tandem U31:G44/G32:U43 pairs that breathe and open frequently, leading to rapid exchange with solvent and peak broadening (figure 1D). Altogether, the NMR data are consistent with the relaxed structure suggested by mutational analysis, NMR, SHAPE, in-line probing and nuclease digestion 7, 23, 35, 40, 41, 44 .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In 15 N- 1 H HSQC spectra recorded at 5C, we also observed four weak and broad peaks with chemical shift values corresponding to tandem U31:G44/G32:U43 pairs that breathe and open frequently, leading to rapid exchange with solvent and peak broadening (figure 1D). Altogether, the NMR data are consistent with the relaxed structure suggested by mutational analysis, NMR, SHAPE, in-line probing and nuclease digestion 7, 23, 35, 40, 41, 44 .…”
Section: Resultssupporting
confidence: 83%
“…Under these conditions, we observe 25% reduction in Dicer processing at 100nM ligand but do not see 50% reduction until nearly 10µM ligand concentration is reached (SI figure 5). These results are surprising, but comparable to those published for Dicer inhibition assays with different chemistries including peptides, small molecules, and even a protein that bind pre-miR21 with low nM affinity 7, 35, 41, 42 . Clearly, inhibition does not match the affinity of the ligands.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…130 If a phage displays a peptide which is a strong ligand of target miRNA, it can be eluted and the peptide sequences responsible for the binding are easily obtained by infecting the specific phage into bacteria and sequencing the relevant part of their viral DNAs. 131 Using this method, Bose et al 132 reported that ‘ALWPPNLHAWVP’ was a potent peptide sequence for binding miR-21. After identifying the binding pocket of this peptide using a PEP-FOLD web server, they further demonstrated that this peptide suppressed tumor cell proliferation, invasion and migration by antiagonizing miR-21.…”
Section: Small Molecule Mirna Therapeutic Agentsmentioning
confidence: 99%
“…122 The peptide miR-21 inhibitor developed by Bose et al has a binding pocket for miR-21 and thus inhibit Dicer processing for miRNA maturation. 132 Nevertheless, there are still general SMIR that inhibits several miRNAs in post-transcriptional process. Watashi et al 142 screened 530 compounds and discovered poly-L-lysine hydrobromide as a Dicer inhibitor and 3,6-diamino-10-methylacridinium chloride as an AGO2 inhibitor.…”
Section: Small Molecule Mirna Therapeutic Agentsmentioning
confidence: 99%